PENGEMBANGAN JIWA KEWIRAUSAHAAN DI KALANGAN MAHASISWA STAIMAS WONOGIRI DENGAN MODEL PEMBELAJARAN BERBASIS PRODUKSI - Amir Mukminin; Eka Yuni Purwanti (PARAMUROBI: JURNAL PENDIDIKAN AGAMA ISLAM, 2021)
The development of the entrepreneurial spirit has become crucial in today's era. Entrepreneurship has become an important authority in society through entrepreneurship will help to open up job opportunities for the community, especially for the development of human resources. This article will discuss the role of STAIMAS Wonogiri to foster motivation and entrepreneurial spirit among students with a production-based learning model. Students have a strategic position to develop entrepreneurial attitudes through entrepreneurship education programs, especially in entrepreneurship practices and job training such as seeking business opportunities through lecturer activities and using industrial cooperation agreements.